2021
DOI: 10.3389/fphys.2021.653349
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveal That Metabolic Improvement Contributes to the Cardioprotective Effect of T89 on Isoproterenol-Induced Cardiac Injury

Abstract: BackgroundT89, a traditional Chinese medicine, has passed phase II, and is undergoing phase III clinical trials for treatment of ischemic cardiovascular disease by the US FDA. However, the role of T89 on isoproterenol (ISO)-induced cardiac injury is unknown. The present study aimed to explore the effect and underlying mechanism of T89 on ISO-induced cardiac injury.MethodsMale Sprague-Dawley rats received subcutaneous injection of ISO saline solution at 24 h intervals for the first 3 days and then at 48 h inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA) was performed using a specific kit indicated by a microplate reader (RT-6100, Rayto, Shenzhen, China), respectively, to determine the content of creatine kinase-MB (CK-MB), troponin T (cTnT), lactic dehydrogenase (LDH), alanine transaminase (ALT), aspartate transaminase (AST), ROS, NO, RNS, IL-1β, IL-18, TNF-α, and IL-6 in plasma (Dogesce Biotech, Beijing, China), and 8-OHdG, malonaldehyde (MDA), and NAD + in the left ventricle (Dogesce Biotech, Beijing, China). Likewise, the activities of caspase-1, MnSOD, and mitochondrial Complexes I, II, IV, and V were also detected using the ELISA kit according to the manufacturer’s instructions ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme-linked immunosorbent assay (ELISA) was performed using a specific kit indicated by a microplate reader (RT-6100, Rayto, Shenzhen, China), respectively, to determine the content of creatine kinase-MB (CK-MB), troponin T (cTnT), lactic dehydrogenase (LDH), alanine transaminase (ALT), aspartate transaminase (AST), ROS, NO, RNS, IL-1β, IL-18, TNF-α, and IL-6 in plasma (Dogesce Biotech, Beijing, China), and 8-OHdG, malonaldehyde (MDA), and NAD + in the left ventricle (Dogesce Biotech, Beijing, China). Likewise, the activities of caspase-1, MnSOD, and mitochondrial Complexes I, II, IV, and V were also detected using the ELISA kit according to the manufacturer’s instructions ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three biological replicates were analyzed, and each sample was adjusted to the same intensity of pooled internal standard within each TMT experiment. Only protein groups without any missing values in all samples were selected for Student’s t -test ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have proved that phytochemicals are capable of mitigating cardiac hypertrophy in cell and animal models via modulating mitochondrial function and maintaining mitochondrial hemostasis. Wei's recent findings suggest that T89, a traditional Chinese medicine, may be a potential therapeutic approach to treat ISO-induced cardiac hypertrophy, and the underlying mechanisms mainly lay on the regulation of metabolic pathways ( 71 ). By performing quantitative proteomics, the group revealed that T 89 could inhibit glycolysis, accelerate fatty acid oxidation and restore mitochondrial OXPHOS, thereby attenuating energy metabolism disorders and alleviating ISO-induced cardiac injury.…”
Section: Potential Therapeutic Approaches Targeting Mitochondria To Prevent or Reverse Cardiac Hypertrophymentioning
confidence: 99%
“…Experimental procedures were approved by the Animal Care Committee of Dongzhimen Hospital Affiliated to the Beijing University of Chinese Medicine (No. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Animalsmentioning
confidence: 99%